PEMBELAJARAN MENULIS TEKS CERITA PENDEK MEGGUNAKAN MEDIA AUDIO VISUAL PADA SISWA KELAS IX SMPN 36 BANDUNG - Nova Siti fatonah; Aditya Permana M.Pd; latifah L (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This study was motivated by students' difficulties in expressing ideas when writing short story texts because the stimulus was less attractive based on the observations made. The purpose of this study was to determine the effect of audio-visual media on learning to write short story texts for class IX students of SMPN 36 Bandung. The research method used is a qualitative method, namely a research approach focused on efforts to gain an in-depth understanding of social phenomena or human behavior from a comprehensive and descriptive perspective. The results of the study showed that 70% of students showed varied vocabulary, 60% of students were able to use sentences effectively, and 70% of students showed high creativity in writing short stories. Even so, there are still students who have less varied vocabulary, less effective sentences, and sufficient or insufficient creativity.